(untitled) (Advances in Applied Mathematics and Mechanics, 2024)
In this work, a new lattice Boltzmann model for a class of viscous wave equation is proposed through the variable transformation, which eliminates the mixed third order partial derivative term of time and space. Some numerical tests are performed to validate the present model, and the results show that the present model has a second-order convergence rate in space.